Statement of consensus on Family Medicine in Africa - Robert (Bob) Mash; Steve Reid (African Journal of Primary Health Care & Family Medicine, 2010)
Family Medicine is an emerging speciality in sub-Saharan Africa and yet potential interest in the contribution of Family Medicine to health, primary care and district health services is limited by the lack of a regional definition. Governments, health departments and academic institutions would benefit from a clearer understanding of Family Medicine in an African context. The 2nd African Regional WONCA (World Organisation of Family Doctors) Conference, held in Rustenberg, South Africa in October 2009, engaged participants from sub-Saharan Africa in the development of a consensus statement on Family Medicine. The consensus statement agreed to by the conference defined the contribution of Family Medicine to equity, quality and primary health care within an African context, as well as the role and training requirements of the family physician. Particular attention was given to the contribution of women in Family Medicine.